(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2018)
The study aims to explore the prospects and retrospects of land use system through agroforestry practices in Meherpur district, Bangladesh. It particularly focuses on some aspects of land uses of the study area like land use pattern, land ownership, choices of species for agroforestry, farmers’ perceptions towards agroforestry, status and prospects of agroforestry practices. This study was carried out by using mixed method followed by a semi-structure questionnaire. A total of 100 respondents were selected by using snowball purposive sampling method. The study revealed that agriculture was the major occupation (50%) of the selected respondents. Of the total land used by selected respondents, 21% land were used for agroforestry, 69% for agriculture and remaining 10% for homestead purposes. Most of the farmers (60%) were small landholders (1 to 5 acres) and 18% had lesser than 1 acre land. Among them 76% had their own land followed by 8% leased land and 16% both own and leased land. They preferred agroforestry in their homestead (92%), agricultural land (65%), water body (31%) and fallow land (18%). The farmers were practicing different types of agroforestry such as cropland, homestead and aquaculture with boundary plantation by mixing trees, agricultural crops and vegetables in their farmlands to receive diversified outcomes. A remarkable change in land use pattern was found after adopting agroforestry practices in this study area. Maximum respondents practiced agro-forestry in their homestead and croplands. Most of the land (67%) was used for agriculture cultivation while a very small amount of land was used as agroforestry in the study area. Int. J. Agril. Res. Innov. & Tech. 7 (2): 1-6, December, 2017